Glycogen Synthase Kinase 3 Inhibition Stimulates Human Cartilage Destruction and Exacerbates Murine Osteoarthritis1. Issue 8 (August 2014) - Litherland, Gary J.; Hui, Wang; Elias, Martina S.; Wilkinson, David J.; Watson, Sharon; Huesa, Carmen; Young, David A.; Rowan, Andrew D.
<x xml:space="preserve">Abstract</x> Objective To assess the role of glycogen synthase kinase 3 (GSK‐3) as a regulator of cartilage destruction in human tissue and a murine model of osteoarthritis (OA). Methods Surgical destabilization of the medial meniscus (DMM) was performed to induce experimental murine OA, and joint damage was assessed histologically. Bovine nasal and human OA cartilage samples were incubated with interleukin‐1 (IL‐1) plus oncostatin M (OSM) and GSK‐3 inhibitor. Collagen and proteoglycan release was assessed by hydroxyproline measurement and dye binding assay, collagenase activity was assessed by bioassay, and gene expression was analyzed by real‐time polymerase chain reaction. Human articular chondrocytes were isolated by enzymatic digestion and cultured prior to gene silencing and immunoblotting of cell lysates and nuclear fractions. Results Mice treated with GSK‐3 inhibitor exhibited significantly greater cartilage damage compared with sham‐operated control mice. GSK‐3 inhibition in bovine cartilage dramatically accelerated IL‐1 plus OSM–stimulated degradation, concomitant with a profound increase in collagenase activity. GSK‐3 inhibitor induced collagen release from human OA cartilage in the presence of IL‐1 plus OSM and increased proteoglycan loss. Gene expression profiling of resorbing OA cartilage revealed a marked procatabolic switch in gene expression upon GSK‐3 inhibition. This was mirrored in human articular chondrocytes following GSK3 silencing, particularly with the GSK‐3β isoform. GSK‐3 inhibition or silencing led to enhanced IL‐1 plus OSM–stimulated abundance and activity of Jun, and silencing of c‐jun ameliorated GSK‐3 inhibitor–mediated procatabolic gene expression. Conclusion GSK‐3 is an important regulator of matrix metalloproteinase (MMP)–mediated joint destruction, the inhibition of which by proinflammatory stimuli de‐represses catabolic gene expression. Therapeutic strategies that maintain cartilage GSK‐3 activity may therefore help curtail aberrant MMP activity during pathologic joint destruction.